양방향 광고의 증강현실 구현을 위한 디지털로봇 활용 연구 - 최치권; 엄기준; Choi, Chi Kwon; Um, Ki Joon ((사)디지털산업정보학회 논문지, 6(3), 2010)
Developments and changes in digital environment based on computer technologies and internet networks enabled us interactive communication for planning and execution through the freedom of 'connection', 'sharing', and 'conversion'. The subject of this study, interactive commercial, might be the core of success based on creation which stems from communication design, revolution in design and technology, and conversion. Communication in modern economy is not optional, but essential. Furthermore, like evolution process up to Augmented Reality from developments of mobile communication technology, or concept in paradigm change, digital interactive commercial means the core of success, not a part of it. Therefore, in order to achieve success in the global competition structure, mobile communication design, revolution, and creation which produce added value shall be working as a base. In order to reach effective communication process performance of interactive commercial media, this study would like to propose building a media commercial system which is realized by human senses. Using this, standardized methods for interactive commercial which can be used together with augmented reality based on digital technology, and for using digital robot contents are available, along with methodology system of their use. In addition, the ultimate goal of this study aims to discover new factors through reorganization of precedent analysis and adaptation based on academic achievement and practical application. And thus, it wants to contribute to practical use of interactive commercial out of augmented reality-based communication in which technology, marketing, and design are integrated to be used in real sense.